ANALISIS YURIDIS PENGATURAN JANGKA WAKTU PENYERAHAN SURAT PEMBERITAHUAN DIMULAINYA PENYIDIKAN OLEH PENYIDIK KEPADA KEJAKSAAN UNTUK MEMULAI PENYIDIKAN BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Brando Pardede; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Implementation of the principles contained in the quick coordination between law enforcement agencies, one of which is an investigator with the prosecutor in the case of submission of the Notice of Commencement of Investigation hereinafter abbreviated SPDP, by the investigator to the prosecutor to initiate an investigation. Fast, should be interpreted as a strategic attempt to make the justice system as an institution that can ensure the accomplishment / achievement of justice in law enforcement quickly litigants. Not only quickly resolved origin are applied but juridical considerations, accuracy, precision, and considerations that guarantee sosilogis sense of justice was also considered. SPDP stipulated in Article 109 paragraph (1) Criminal Code, namely: